God Fights to Save the Nation of Israel: A Historical-Critical Review of Exodus 15:1-21 - Tambun, Roy Haries Ifraldo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
In the context of Israel’s liberation from Egyptian slavery, God is depicted as the victor who defeats Pharaoh through the drowning of the Egyptian army in the Red Sea. God's power, surpassing that of Egypt, underscores that this deliverance was entirely the result of His might, without direct intervention from the people of Israel. Through the narrative of Exodus 15:1-21, the author highlights the relationship between the song of salvation sung by Moses and Miriam and the destruction experienced by Egypt. This song is an expression of gratitude for the victory granted by God, showing His favor towards the Israelites. The author hypothesizes that the destruction of the enemy is a manifestation of God’s glory as a Divine Warrior, who fights against sin and brings salvation to His people. The theoretical framework includes an etymological and terminological analysis of the concepts of warfare, salvation, and song in the biblical context. Warfare is seen as a divine act to display God's glory through victory over enemies. Salvation is understood as liberation from both physical and spiritual oppression, ultimately fulfilled in the name of Jesus Christ. Song, as an expression of thanksgiving, reinforces the theme of salvation in the Exodus narrative, where the Israelites celebrate their deliverance by praising God. Overall, this study affirms that the event of Israel’s liberation is central to the Old Testament’s salvation history, with God serving as the Savior and Warrior who brings victory to His people.